Simultaneous determination of phosphodiesterase-5 (PDE-5) inhibitors and their analogues in sexual enhancement products / Nur Baizura Bujang - Nur Baizura, Bujang (2018)
Adulteration of herbal health supplements (HHSs) with phosphodiesterase-5 (PDE-5) inhibitors and their analogues is becoming a worldwide problem. These HHSs are marketed for increasing sexual performance, in men. In legal medical practice, PDE-5 inhibitors are only used to treat patients with erectile dysfunction (ED), but these adulterated HHSs are also being utilised by men without ED for recreational purposes. Screening the presence of these adulterants is important to protect the safety of consumers. However, the complexity in managing this adulteration problem involve many different aspects including the ever increasing number of new analogues, the budget restriction in obtaining the reference standards for these analogues and the method needed to simultaneously detect all PDE-5 inhibitors and their analogues. In order to develop the capability to produce in-house standards, ten sildenafil analogues were synthesised. The purity of the synthesised standards was above 90%. These synthesised standards together with fifty-one commercial reference standards of PDE-5 inhibitors and their analogues were then used to build a LCMS spectral library. A LCMS IT-TOF method was developed and validated for simultaneous determination of the sixty-one standards. The determination method was applied to investigate adulterated HHSs sold in the Malaysian market. Sixty-two products that claim to enhance men’s sexual health were sampled between April 2014 and April 2016. These products included unregistered products seized by the Pharmacy Enforcement Division of the Ministry of Health (n = 39), products sent to the National Pharmaceutical Regulatory Agency for preregistration testing (n = 9) and products investigated under the post-registration market surveillance programme (n = 14). The products were tested against the in-house spectral iv library consisting of 61 PDE-5 inhibitors and analogues using the validated LCMS ITTOF method. Thirty-two (82%) of the unregistered products and two (14%) of the registered products were found to be adulterated with at least one PDE-5 inhibitor or analogue, while none of the pre-registration products contained the adulterants of our interest. A total of 16 different adulterants were detected and 36% of the adulterated products contained a mixture of two or more adulterants. Two of the adulterants, which were not included in the spectral library, were identified as acetil acid and xanthoantrafil using the formula predictor software included in the LCMS IT-TOF system. In conclusion, this study has demonstrated that the adulteration of unregistered herbal products in the Malaysian market is an alarming issue that needs to be urgently addressed by the relevant authorities.